THE INFLUENCE OF DIGITAL PAYMENT ON CONSUMPTIVE BEHAVIOR (Case Study Students of the Faculty Economics, Unived Bengkulu) - Sulisti Afriani; Rina Trisna Yanti (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
Digital Payment transactions are the most widely used today, because they are easier to use, can be done anywhere and anytime and are safer than cash. This provides convenience and security for digital payment users. This study aims to determine the influence of digital payments on consumptive behavior in students of the faculty of economics, Dehasen University Bengkulu. The sample used in this study was class A management students who were in the class of 2021 and 2022 totaling 105 respondents. The data collection method is carried out using a questionnaire that is distributed through an online google form. Regression equation is as follows: Y = 8,985 + 0,680X, The correlation coefficient is obtained r = 0,604 lies between level 0,600 - 0,799 including in strong correlation, R Square of 0,365 means the digital payment conduct variable can be influenced by the consumptive behavior variables of 60,4%. While the remaining 39,4 % can be influenced by other variables not examined by this study. Because the value of α < 0,05 it can be concluded that the digital payment variable partially affect consumptive behavior conduct, meaning the proposed hypothesis acceptable, this means accepting Ha and rejecting Ho. Keywords: digital payment, consumptive behavior